Immunocorrective treatment use in the prevention of hematological and infectious complications of chemotherapy in cancer patients - L. Yu. Grivtsova; V. B. Larionova; N. A. Falaleeva (Онкогематология, 2021)
The article analyzes the use of immunocorrection of hematological toxicity that occurs during chemotherapy in cancer patients. Hematological toxicity, along with cardiotoxicity and hepatotoxicity often prevents the implementation of the entire planned volume of chemotherapy.Standard therapy (colony stimulating factor use) may not be always available and there is a need to develop new and more effective strategies for supportive care. Among the various methods and approaches, the most promising may be the use of systemic immunecorrecting therapy, the possibilities of which are far from being realized in oncological practice.The analysis of the studies summarized in this review demonstrates the effectiveness of the immunomodulator/immu‑ noadjuvant – azoximer bromide in hematological toxicity prevention in patients with various types of cancer.